Self-determined goals in a solution-focused batterer intervention program: Application for building client strengths and solutions. Issue 6 (17th August 2016) - Bolton, Kristin Whitehill; Lehmann, Peter; Jordan, Catheleen; Frank, Laura; Moore, Blaine
ABSTRACT: The present study explores the content and characteristics of self-determined goals developed by violent offenders as part of a court-mandated treatment program. Data were collected from 89 domestic violence offenders enrolled in a solution-focused batterer intervention program. The data were analyzed using content analysis, and the emergent themes included (1) emotional regulation, (2) personal growth, (3) improve family relationships, and (4) improve communication. The findings from this study offer preliminary insight into the type of goals, the usefulness and importance of developing goals, and how goals might be helpful in reinforcing the change process while in treatment.